Clinical Characteristics And Inflammatory Biomarkers Of Hospitalized Children With Hand, Foot, And Mouth Disease: A Case Series - Anggita Dian Karera; Delta Iswara (International Journal of Health Engineering and Technology, 2026)
Hand, foot, and mouth disease (HFMD) is an acute viral infection that commonly affects young children. Although the disease is usually self-limiting, some patients require hospitalization due to decreased oral intake and dehydration. Data on the clinical and laboratory characteristics of hospitalized HFMD patients remain limited. This retrospective case series analyzed medical records of pediatric HFMD patients hospitalized at RSU An Ni'mah Wangon Banyumas from January 2024 to November 2025. Demographic characteristics, clinical manifestations, length of stay, and laboratory findings were collected. Inflammatory biomarkers including neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) were calculated. Data were analyzed descriptively. A total of 11 patients were included with a median age of 33 months (range 16–121 months). Most patients were younger than 36 months (63.6%), and 72.7% were female. The median length of hospital stay was 4 days (range 2–8 days). All patients presented with fever and oral lesions, while hand and foot lesions were observed in 81.8% and 90.9% of cases. Gastrointestinal symptoms were present in several patients. Laboratory findings were generally within normal ranges, with a median NLR of 2.76 and PLR of 160. One patient had dengue coinfection. Hospitalized HFMD patients commonly present with typical clinical features and favorable outcomes with supportive treatment. Inflammatory biomarkers such as NLR and PLR may reflect the inflammatory response in HFMD.